2023
DOI: 10.1002/aic.18316
|View full text |Cite
|
Sign up to set email alerts
|

CAPBO: A cost‐aware parallelized Bayesian optimization method for chemical reaction optimization

Runzhe Liang,
Haoyang Hu,
Yueheng Han
et al.

Abstract: Bayesian optimization employs probabilistic surrogate models to effectively address expensive and time‐consuming closed‐loop chemical experimental design. However, traditional Bayesian optimization focuses on reducing the number of iterations and follows an inherently sequential process (with one new data point sampled in each iteration), which is an inefficient means of exploiting and characterizing reactions using parallel microreactors. In this article, we present an approach that overcomes this issue by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In contrast, traditional Bayesian optimization approaches are typically sequential in nature, although ongoing research is addressing this limitation. 41,42 Specific SNOBFIT algorithm details for both case studies, including parameter settings and implementation specifics, can be found in the ESI †…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, traditional Bayesian optimization approaches are typically sequential in nature, although ongoing research is addressing this limitation. 41,42 Specific SNOBFIT algorithm details for both case studies, including parameter settings and implementation specifics, can be found in the ESI †…”
Section: Methodsmentioning
confidence: 99%